The origins of the transitional programme - Gaido, Daniel Fernando (2018)
The origins of the Transitional Programme in Trotsky’s writings have been traced in the secondary literature. Much less attention has been paid to the earlier origins of the Transitional Programme in the debates of the Communist International between its Third and Fourth Congress, and in particular to the contribution of its largest national section outside Russia, the German Communist Party, which had been the origin of the turn to the united-front tactic in 1921. This article attempts to uncover the roots of the Transitional Programme in the debates of the Communist International. This task is important because it shows that the Transitional Programme’s slogans are not sectarian shibboleths, but the result of the collective revolutionary experience of the working class during the period under consideration, from the Bolshevik Revolution to the founding conference of the Fourth International (1917–38).